Mindfulness as Predictor of Itch Catastrophizing in Patients With Atopic Dermatitis: Results of a Cross-Sectional Questionnaire Study - Lüßmann, Kjell; Montgomery, Kerry; Thompson, Andrew; Gieler, Uwe; Zick, Christoph; Kupfer, Joerg; Schut, Christina (Frontiers in Medicine, 2021)
Itch and worry about itch are predominant symptoms in atopic dermatitis (AD). Mindfulness refers to paying attention in a certain way, non-judgementally and on purpose. In patients with chronic pain, which shares several similarities with chronic itch, a relationship between pain intensity, mindfulness and pain catastrophizing has been found. The aim of this study was to investigate whether itch intensity and mindfulness are related to itch catastrophizing in AD patients. Participants receiving treatment for AD (n=155; 58 male; mean age: 46.5 ± 12 years) completed measures of itch-related catastrophizing (Itch Cognitions Questionnaire; ICQ) and mindfulness (Comprehensive Inventory of Mindfulness; CHIME) during their stay at a rehabilitation centre in Borkum, Germany. In addition to other variables, their average itch intensity during the last two weeks was assessed by means of a visual analogue scale. A positive relationship between itch intensity and itch catastrophizing was found (r=0.409; p < 0.01). Moreover, the mindfulness scales ‘acting with awareness’, ‘accepting and non-judgemental orientation’, and ‘non-reactive orientation’ were negatively related to itch catastrophizing. A linear regression analysis revealed that itch intensity in combination with ‘acting with awareness’ was able to explain more than 27 % (corrected R2 = 0.274; p < 0.001) of the variance of itch catastrophizing. Thus, itch intensity and certain facets of mindfulness were associated with itch catastrophizing in AD patients. Psychological interventions aiming to increase acting with awareness might have a buffering effect on itch catastrophizing, which in turn could lead to lower itch intensity in patients with AD. Future RCTs should test this hypothesis.